Investigating strategic management roles of the corporate communication function in the Department of Housing - Benita Steyn; Mateboho Green (Communicare)
The first phase of this qualitative study employed the extended case method. Its aim was to explore the role behaviour of the most senior corporate communication practitioner in the government Department of Housing, South Africa. It was found that the Director: Communication Services played a combination of roles: firstly, Dozier's (1984) media relations specialist (seen as part of the historic technician role) and secondly, she also performed certain generic managerial activities. The two (new) strategic management roles of the corporate communication function, the strategist and the redefined manager, were not observed (Steyn, 2000a; 200Gb). The second phase entailed the development of a corporate communication strategy for the Department by the Deputy Director, using action research. The unit of analysis was her communicative output, in the form of the strategy. Empowered by postgraduate studies, she was found to possess the necessary strategic communication management knowledge and skills to perform this important activity of a practitioner in the redefined role of manager successfully.